Investment Between Growth And Development, With Reference To The Reality Of The Kurdistan Region Of Iraq - Lara Bwrhan Sabir; Zakia Abdalmnem Qoja; Nida Saleem Mala Younis (QALAAI ZANIST JOURNAL, 2024)
Investing in growth and development refers to the process of directing financial liquidity and other resources towards projects and activities that enhance economic growth and contribute to the comprehensive development of society. Investment is a key driver of economic and social development in developing countries and emerging regions.Regarding the Kurdistan Region of Iraq, investment can play an important role in promoting economic growth and improving the living conditions of the population. The advantage of relative stability and strategic location of the Kurdistan Region could attract investments from the private and public sectors, both from inside and outside Iraq. Investment challenges in the Kurdistan Region may include political and security stability, economic challenges such as weak infrastructure and lack of basic services, in addition to social and cultural challenges. It is important to develop effective policies and strategies to attract investments, strengthen the business environment, enhance education and vocational training for the local workforce, enhance infrastructure, and provide basic services to support sustainable economic growth and development in the Kurdistan Region and in Iraq in general. The reality of investment in the region from 2006 to 2023 was presented in terms of the number of investing companies and their capital relative to the sectors. One of the most important conclusions we reached is the most important factors (sectors) that affect revenues, expenditures, and growth, which are the banking sector, the commercial sector, and the education sector.